The Departure Point in Raising Teacher’s Awareness toward the Atmosphere of Lingua Franca Case - Ambar Jati; Endang Fauziati; Sri Samiati Tarjana (Indonesian Journal of EFL and Linguistics, 2020)
There has been growing attentiveness in the English teaching literature of the prominence of English as Lingua Franca (ELF). The foremost position of English as language of global citizen should be raised up in the communication traffic in the world. Research under the case study design had been done to reveal teacher’s belief and their responses in the wave of English as Lingua Franca features in expanding circle, Indonesia. The researchers conducted the study at an Indonesian International School in Surakarta which involved two teachers as the participants by employing interview and unstructured questionnaire to collect the data. The result evidently showed that teachers in expanding circle were aware about the evolvement of English as Lingua Franca in the world. They believed that the features of English as Lingua Franca (ELF) are unproblematic as long as it does not change the fundament of their utterances. Henceforth, the teachers support the lexico-grammar features of ELF. In their speaking class, teachers give tolerance to the students who appearing these features in their classroom interaction. Furthermore, the result of this research could inspire other teachers to be more aware toward the evolvement of ELF, so that they could integrate and apply the relevancy of ELF in teaching learning process.